(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study was aimed at determining the optimum ratio of energy and protein to promote optimal growth of grower pullet chickens that will give optimum layer performance in terms of egg production, weight, quality and to compare the cost implications of the various energy protein ratios. The following parameters were used: feed intake, bodyweight gain, feed conversion ratio and water intake. Two hundred and seventy (270) grower pullet chickens (Isa Brown), were randomly allocated into nine treatments at 30 birds per treatment. Each treatment was replicated three times in RCBD involving 3×3 factorial arrangement. The grower pullet chickens were fed nine treatment diets containing 3 energy levels (2500, 2700 and 2900 ME (kcal/kg) and 3 crude protein levels (14, 15 and 16%). Feed and water were given ad libitum. Feed intake, body weight gain, feed conversion ratio and water intake of grower pullet chickens were significantly (P<0.05) influenced by energy-protein ratios. Feed intake decreased with increase in energy-protein ratio of the diets. Grower pullets fed diets containing 2500 and 2700 ME (kcal/kg) diet at14% CP recorded low feed intake, body weight gain, water intake and feed cost/kg gain compared to others while those on 2700 ME (kcal/kg) diet at 14% CP showed lower FCR. Based on the results of this study, it was concluded that the body weight of grower pullets was better controlled on 2700 ME (kcal/kg) diet at 14% CP. Hence, it is therefore recommended.